Application of RFID Technology in Libraries (International Journal of Innovative Research in Computer Science & Technology, 2020)
Librarians are recognized for being early  adopter’s technologies, but they've begun to use RFID to  deliver more efficient as well as effective circulation  services, as well as to protect library assets. Despite the  fact that RFID adoption in libraries has increased  significantly in recent years, the expense of the  technology, the lack of standards, as well as privacy  protection remain key hurdles to additional libraries  adopting it. In terms of budgetary restrictions, if libraries  adopt such technologies, the increases the quality of  "Return on Investments" might be obtained, as it would  speed up the circulating process by allowing employees  to engage in the other user behavior. Libraries that wish  to utilize RFID need to use ISO 28560 compatible RFID  tags in combination to ISO 15693, ISO 18000-3, as well  as other NISO-established worldwide guidelines due to  the absence of standardization. Libraries should follow  industry standards and keep no personal information on  RFID tags to preserve users' privacy. Whether or whether  libraries utilize RFID technology now, they won't be able  to escape it in the future since book wholesalers offer  publications which have already been identified for free.  RFID is the newest technology used in library theft  detection methods (Radio Frequency Identification).  Apart from EM (Electro-Mechanical) and RF (Radio  Frequency) systems, which have long been used in  libraries, RFID-based systems go beyond security to be  become traceability capable of integrating security with  much more efficient resources monitoring all through the  library, such as easier and quicker charge as well  as discharge, inventory, and handling of materials.
Keywords: Library; RFID; Radio Waves; Security; Tag